All quiet on the western front [videorecording (DVD)] - Wolheim, Louis; Ayres, Lew, 1908-1996; Milestone, Lewis, 1895-1980; Remarque, Erich Maria, 1898-1970 (Universal Home Video, 1999)
A group of young World War I German recruits pass from idealism to disillusionment with war.